Juridical Analysis of Land Ownership Discrepancies in Certificates and SPPT Legality in Lemahmakmur Village Based on Regulation 24/1997 - Abas, Muhamad; Putra, Affian Fandi; Himim, Aldora Ananda Putra; Nurfadilah, Intan Elga; Fauzi, Muhammad Iqbal; Dwi Permata, Sagita (Jurnal Hukum dan Keadilan, 2024)
Lemahmakmur village as one of the villages in Karawang district, has great potential in the agricultural sector, however, there is a problem related to land ownership in the village, namely the difference in name between the certificate and the Tax Payable Notification Letter (SPPT). The research method used is an empirical legal method and uses a qualitative approach, by conducting interviews with village officials and residents in Lemahmakmur village. Plus using previous book and journal sources regarding this publication. Data obtained from literature such as books are secondary data sources used in this study. Secondary data sources include primary legal materials, secondary legal materials and tertiary legal materials. This study aims to analyze the implications of differences in names in certificates and Tax Payable Notification Letters (SPPT) on land legality in Lemahmakmur village. Lemahmakmur village, like many villages in Indonesia, has experienced the phenomenon of differences in names on certificates and Tax Payable Notification Letters (SPPT) after the implementation of the PTSL program. Article 3 letter a of PP No. 24/1997 is a fundamental basis for understanding the root of the problem of differences in names between certificates and SPPT. This article explicitly states that the purpose of land registration is to ensure legal certainty regarding land rights, in practice the Complete Systematic Land Registration (PTSL) process in Lemahmakmur village does not fully meet this objective. Several impacts arise, including legal impacts, economic impacts, and social impacts.